2014
DOI: 10.4236/jcpt.2014.44026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Struvite-k Crystals by Agar Gel

Abstract: The phosphate mineral struvite is basically formed in urinary tracks and kidney. One of the analogous compounds of struvite is potassium magnesium phosphate hexahydrate (KMgPO 4 •6H 2 O), known as struvite-k crystal and found in animal urinary calculi. In the present investigation, struvite-k crystals were grown by single diffusion and double diffusion techniques in agar gelmedium. The grown crystals were analyzed by optical microscopy, scanning electron microscopy (SEM), fourier transform infrared (FTIR) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, the NH 4 + component of its structure can be readily replaced by K when this ion is present in high concentrations in solution. In this way, potassium struvite can be formed (MgKPO 4 • 6H 2 O) [15,16]. Besides P, the solubilisation of struvite is also an important source of Mg and K/NH 4 for crop plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, the NH 4 + component of its structure can be readily replaced by K when this ion is present in high concentrations in solution. In this way, potassium struvite can be formed (MgKPO 4 • 6H 2 O) [15,16]. Besides P, the solubilisation of struvite is also an important source of Mg and K/NH 4 for crop plants.…”
Section: Introductionmentioning
confidence: 99%
“…There are some fine particles for dental stone as well related to the other component of stone (can be seen in Figure 2(a) ). Suryawanshi et al reported a similar morphology for calcium sulfate stones and the reason for the existing morphology was the presence of multidimensional sloping micro-circular crystals of calcium sulfate [ 16 ]. SEM results showed that after the addition of nanoparticles, there were no significant morphological changes in stone compared to the control group (stone without nanoparticles).…”
Section: Resultsmentioning
confidence: 99%
“…The 'stones' formed under acidic condition by addition of 0.25 M HCl were confirmed by powder X-ray diffraction (PXRD) analysis to be newberyite (magnesium hydrogen phosphate trihydrate; MgHPO 4 Á3H 2 O), an essential constituent in animal urinary calculi that precipitates at pH below 6 and is commonly found as spherules (Fig. 3b) (Suryawanshi & Chaudhari, 2014). Similarly, crystals of strontium oxalate, an isomorphic compound of weddelite, grew in an agar gel containing strontium chloride and covered with a solution of oxalic acid, both at 2 M (Fig.…”
Section: Figurementioning
confidence: 96%
“…Although the growth of struvite microcrystals by a simple diffusion technique in agar gel was not successful, one of its analogs, struvite-K (potassium magnesium phosphate hexahydrate; KMgPO 4 Á6H 2 O), gave crystals and was used for further analysis (Figs. 3a and 3b) (Sun et al, 2010;Suryawanshi & Chaudhari, 2014;Henisch, 1996). The effect of variation of pH on the growth of struvite-K crystals was investigated to test the potential preventive effects of alkalization on stone formation.…”
Section: Representative Student Projectsmentioning
confidence: 99%
See 1 more Smart Citation